2010
DOI: 10.1063/1.3473825
|View full text |Cite
|
Sign up to set email alerts
|

Small angle neutron scattering from 1-alkyl-3-methylimidazolium hexafluorophosphate ionic liquids ([Cnmim][PF6], n=4, 6, and 8)

Abstract: The presence of local anisotropy in the bulk, isotropic, and ionic liquid phases-leading to local mesoscopic inhomogeneity-with nanoscale segregation and expanding nonpolar domains on increasing the length of the cation alkyl-substituents has been proposed on the basis of molecular dynamics (MD) simulations. However, there has been little conclusive experimental evidence for the existence of intermediate mesoscopic structure between the first/second shell correlations shown by neutron scattering on short chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
279
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 279 publications
(301 citation statements)
references
References 54 publications
21
279
1
Order By: Relevance
“…Since the position of the boson peak and sound velocity [63][64][65]81 of ionic liquids are more dependent on anion than cation, the length ξ does not change with the length of the alkyl chain in 1-alkyl-3-methylimidazolium cations, in contrast to the position of the first-sharp diffraction peak observed in static structure factor of ionic liquids. 26,[66][67][68] After normalizing the spectra by the high-frequency intramolecular bands of the common [Tf 2 N] anion, we found that the low-frequency Raman spectra of ionic liquids based on imidazolium cations are significantly less intense than ionic liquids containing non-aromatic cations. This is expected because of the more polarizable moiety of the imidazolium ring, but an interestingly finding is that the relaxational and vibrational contributions change by the same amount among the aromatic and nonaromatic ionic liquids investigated in this work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the position of the boson peak and sound velocity [63][64][65]81 of ionic liquids are more dependent on anion than cation, the length ξ does not change with the length of the alkyl chain in 1-alkyl-3-methylimidazolium cations, in contrast to the position of the first-sharp diffraction peak observed in static structure factor of ionic liquids. 26,[66][67][68] After normalizing the spectra by the high-frequency intramolecular bands of the common [Tf 2 N] anion, we found that the low-frequency Raman spectra of ionic liquids based on imidazolium cations are significantly less intense than ionic liquids containing non-aromatic cations. This is expected because of the more polarizable moiety of the imidazolium ring, but an interestingly finding is that the relaxational and vibrational contributions change by the same amount among the aromatic and nonaromatic ionic liquids investigated in this work.…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72][73] On the other hand, the FSDP in ionic liquids has been recently assigned to correlation of the second shell of cations, with no need of a picture of nanoscale polar/non-polar heterogeneity. 68 However, it is worth stressing that the physical picture of structural heterogeneity in ionic liquids has been proposed by MD simulation not only on the basis of the occurrence of a FSDP in the calculated S(k) but also on the basis of anions depletion in regions occupied by the alkyl chains. [70][71][72][73] Several inorganic glass-formers present correlation between the characteristic length ξ obtained from the boson peak and from the FSDP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of such amphiphilic ions include alkyl sulfate anions and tetraalkyl-ammonium or phosphonium cations. When the alkyl tails on such anions or cations are long enough, a characteristic peak in the observed liquid structure function, the so-called first sharp diffraction peak (FSDP) is routinely observed both in X-ray and neutron scattering 7,8 as well as in molecular simulations. 9 For a cationic hydrocarbon chain of length n = 5 or longer, the FSDP has been shown to lead to nanoscale phase segregation between polar head groups and non-polar alkyl tails.…”
Section: Introductionmentioning
confidence: 99%